Mitigating circumstances in death penalty decisions: using evidence-based research to inform social work practice in capital trials - Schroeder, Julie (2006)
Providing an effective defense for individuals charged with capital crimes requires a diligent, thorough investigation by a mitigation specialist. However, research suggests that mitigation often plays a small role in the decision for life. Jurors often make sentencing decisions permatgurely, basing those decisions on their personal reactions to the defendant (for example, fear, anger), their confusion about the rules of law, and their lack of understanding regarding their role and responsibilities. This article proposes an evidence-based conceptual model of the complicating problems surrounding mitigation practice and a focused discussion about how traditional social work mitigation strategies might be evolved to a set of best practices that more effectively ensure jurors' careful consideration of mitigation evidence. - Reproduced.
Keywords: Penal sanctions